Pengembangan Ethnoscience Puzzle Guna Mendorong Kemampuan Kognitif Anak Berkebutuhan Khusus - Oktaviani, Eva; Setiyono, Imawan Eko (Journal of Telenursing (JOTING), 2023)
This research aims to develop an ethnoscience puzzle educational game tool to encourage the cognitive abilities of Children with Special Needs (ABK) in special schools. The method used in this research uses Research and Development (R&D) with a 4D approach, namely defining, designing, developing, and disseminating. The results of the expert validation test show that the ethnoscience puzzle is excellent and suitable for use as an educational game tool to improve the cognitive abilities of ABK. A limited trial was carried out on 20 crew members at the elementary school level, and the results showed that most crew members' cognitive assessments did not understand (TMS). Still, they understood (M) after playing using the ethnoscience puzzle. Conclusion: The ethnoscience puzzle game positively influences the cognitive development of ABK. Keywords: Children with Special Needs, Ethnoscience Puzzle, Special Schools